2010
DOI: 10.1007/s13312-011-0084-z
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate self harm in children

Abstract: Deliberate self harm occurs in young children and the risk factors are comparable to those in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 19 publications
3
30
1
Order By: Relevance
“…Slightly more than one-fifth of the patients had diagnosable psychiatric illness in the present study, this is less that the reported range of 30-52% in previous studies from India[1217] which have studies children and adolescents presenting with attempted suicide or deliberate self-harm. In the present study, about one-tenth of patients had family history of alcohol dependence, which has been identified as a risk factor for self-harm in adolescents.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Slightly more than one-fifth of the patients had diagnosable psychiatric illness in the present study, this is less that the reported range of 30-52% in previous studies from India[1217] which have studies children and adolescents presenting with attempted suicide or deliberate self-harm. In the present study, about one-tenth of patients had family history of alcohol dependence, which has been identified as a risk factor for self-harm in adolescents.…”
Section: Discussioncontrasting
confidence: 83%
“…[12161920] This suggests that there is a need to expand the literature on this topic. Accordingly, the aim of this retrospective chart review was to study the socio-demographic and clinical profile of children and adolescents presenting with intentional self-harm and referred to psychiatry consultation liaison (CL) services for evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…[2] In many studies of deliberate self-harm, academic pressure was found to be associated with suicidal ideas and occurrence of deliberate self-harm. [2][3][4] Suicide is considered to be the second most common cause of death in adolescents in industrialized countries, and high rates are reported from India as well. [5,6] The present study was planned to determine levels of stress in school students, their psychological health, and prevalence of suicidal ideas among them and any correlation between these variables.…”
Section: Introductionmentioning
confidence: 99%
“…Poisoning in older children and adolescents is more often intentional, especially due to increasing stress. 15,16 The most common cause of acute medical illness in many countries has been exposure to toxic substances. 9,[17][18][19][20] General epidemiological data should be used to assist emergency department on proper management of poisoning cases especially for effective preventive and therapeutic approaches.…”
mentioning
confidence: 99%